Stabilizing oxygen intermediates on redox-flexible active sites in multimetallic Ni–Fe–Al–Co layered double hydroxide anodes for excellent alkaline and seawater electrolysis. Issue 48 (31st October 2021) - Enkhtuvshin, Enkhbayar; Kim, Kang Min; Kim, Young-Kwang; Mihn, Sungwook; Kim, So Jung; Jung, Sun Young; Thu Thao, Nguyen Thi; Ali, Ghulam; Akbar, Muhammad; Chung, Kyung Yoon; Chae, Keun Hwa; Kang, Sukhyun; et al.
Abstract : Quaternary multimetallic LDHs have been developed through a facile metal–organic-framework derived electrochemical activation process. Ni–Fe–Al–Co quaternary LDHs show one of the best OER performances in alkaline and seawater electrolytes. Abstract : Development of an efficient and stable electrocatalyst for the oxygen evolution reaction (OER) is crucial to generate hydrogen via water splitting as a sustainable fuel. Nickel iron layered double hydroxides (NF-LDHs) are considered the most promising electrocatalysts for alkaline water oxidation among various low-cost transition metal-based electrocatalysts although exact mechanisms are still on debate. Herein, we disclose that quaternary multimetallic Ni–Fe–Al–Co LDHs (NFAC-MELDHs) function as one of the best catalysts for alkaline as well as seawater oxidation due to the synergetic effects among the four different redox-flexible metals. The multimetallic Ni–Fe–Al–Co LDHs are prepared via the metal–organic framework (MOF)-derived electrochemical incorporation of fourth transition metal (Co) into ternary Ni–Fe–Al LDHs grown by a hydrothermal reaction. Moreover, we reveal an exact electrocatalytic mechanism for the OER in NFAC-MELDHs via ex situ spectroscopies in combination with density functional theory (DFT) calculations. Redox-flexible Fe is identified with a real active site in synergy with the neighboring metals stabilizing adsorption of oxygen intermediates and simultaneously facilitating charge transfer. In consequence, NFAC-MELDHs exhibit one of the lowest overpotentials of 220 and 280 mV for affording a current density of 100 mA cm −2 in alkaline and simulating seawater solutions, respectively. More importantly, activity and stability merits in electrocatalysis for the OER are improved in the sequence of unary, binary, ternary, and quaternary LDHs, implying that catalyst design using multimetals for LDHs is a highly promising strategy.